Financial literacy, access to finance and financial performance of youth-led Small and Medium-sized Enterprises (SMEs): evidence from Gulu City, Uganda / Kizito Emmanuel Nyeko ... [et al.] - Nyeko, Kizito Emmanuel; Voon, Mung Ling; Ngui, Kwang Sing; Lim, Tze Yin (Universiti Teknologi MARA, Terengganu, 2024)
The study examined the financial literacy, access to finance, and financial performance of youth-led Small and Medium-sized Enterprises (SMEs) in Gulu City, Uganda. This research utilised self-administered questionnaires distributed to 213 youth-led SME management teams/owners. Multiple regression analysis was employed to test the influence of financial literacy and access to finance on the financial performance of enterprises, considering characteristics specific to the youth owner/management teams and the unique features of youth-led SMEs. The findings indicated that financial literacy and access to finance both positively and significantly impact the financial performance of youth-led SMEs. Youth owner/management teams with strong financial literacy skills and access to finance are better equipped to understand enterprise-related business concepts and manage their investments, budgeting, debt management, savings, financial goals, and risk management, all of which contribute to the financial performance of their enterprises. Additionally, this study extended the current literature by providing empirical evidence that validates the Resource-Based View (RBV) theory from the perspective of enterprises in developing nations. The findings suggest that Government Ministries, Departments and Agencies (MDAs), academia, and business associations should proactively promote Public-Private Partnerships (PPPs) to create initiatives for skilling the youth through formal and informal education ensuring the sustainable financial performance of youth-led enterprises.